Malaysian consumers' willingness-to-pay toward eco-labeled food products in Klang Valley - Mohamed, Zainal Abidin; Phuah, Kit Teng; Rezai, Golnaz; Sharifuddin, Juwaidah (Routledge, 2014)
Food labeling is an important aspect of food law that provides consumers with information about food products, and eco-labeling is one such tool for conveying that information. The products that are produced under environmentally friendly and sustainable practices can qualify to apply for eco-label certification. The purpose of this article is to investigate how much consumers are willing to pay for eco-labeled food products in Malaysia. A survey was conducted in Klang Valley, Malaysia, and 1,115 respondents were interviewed using a structured questionnaire. Consumers’ willingness to pay for eco-labeled food products is determined by using contingent valuation method (CVM). Theory of planned behavior (TPB) is chosen for use in this study. Descriptive analysis summarizes the sociodemographic data, and binary logistic model is used to identify consumers’ sociodemographic factors, past experience, and knowledge in predicting the likelihood of willingness to pay for eco-labeled food products. The results indicate that education level, income, age, marital status, household size, attitude, past experience, and knowledge significantly influence consumers’ willingness to pay for eco-labeled food products.